PENGEMBANGAN MEDIA POP – UP BOOK BERBASIS APLIKASI POWERPOINT MATERI BANGUN DATAR PADA PEMBELAJARAN MATEMATIKA SISWA KELAS IV SD - Rendi Marlianda; Riza Fadli; Wilidia (STKIP Subang, 2024)
There are problems in mathematics learning, namely low student learning outcomes in mathematics subjects involving flat shapes including squares, rectangles, triangles, parallelograms, trapezoids, kites, rhombuses.This research is a type of research and development using the ADDIE model which was developed by the learning technology center at the University of Florida for the United States military service. These models are: 1) analysis, aimed at collecting data that characterizes the media being developed, 2) Design, designing a pop-up book media that will be used by researchers, 3) development, aimed at developing valid pop-up book media, practical and effective, 4) implementation, aims to document learning media procedures and, 5) evaluation, aims to determine students' knowledge after studying flat shape material using pop-up book media. The results of this research state that the pop-up book media on flat material is as follows: 1) the pop-up book media on flat building material is in very valid criteria because it is in accordance with the characteristics of class IV students, so it is suitable for use, 2) pop-up media flat shape material book for grade IV elementary school students is in very practical criteria, with the characteristics of being easy to understand, interesting, and can be applied by teachers and students, 3) the pop-up media book for flat shape material for class IV elementary school students is effective for learning outcomes about flat shapes, namely squares, rectangles, triangles, parallelograms, trapezoids, rhombuses and kites.